One‐Year Follow‐Up After Single Procedure Cryoballoon Ablation: A Comparison Between the First and Second Generation Balloon. (9th April 2014) - GIOVANNI, GIACOMO DI; WAUTERS, KRISTEL; CHIERCHIA, GIAN‐BATTISTA; SIEIRA, JUAN; LEVINSTEIN, MOISES; CONTE, GIULIO; DE ASMUNDIS, CARLO; BALTOGIANNIS, GIANNIS; SAITOH, YUKIO; CICONTE, GIUSEPPE; JULIA, JUSTO; MUGNAI, GIACOMO; et al.
A Comparison Between the First and Second Generation Balloon Background With respect to the first generation Cryoballoon (CB), the second generation (Cryoballoon Advance [CB‐A], Medtronic, Minneapolis, MN, USA) was designed with technical modifications resulting in a larger and more uniform zone of freezing on the balloon's surface aiming at procedural outcome improvement in the setting of atrial fibrillation (AF) ablation. However, a comparison between both technologies on a midterm follow‐up is missing in today's literature. Methods A total of 100 patients (the last 50 patients with the first generation CB and the first 50 patients with the second generation CB‐A upon its inception in our center) having undergone a single CB ablation for paroxysmal AF (PAF) and having completed a 12‐month follow‐up, were consecutively included in our study. Freedom from AF off‐antiarrhythmic drugs (AADs) after a single procedure was 78% (39/50) in CB‐A and 58% (29/50) in the CB group (P = 0.03) during the whole follow‐up duration. Considering a blanking period of 3 months, freedom from AF off‐AAD was achieved in 84% (42/50) in CB‐A, while 66% (33/50) were free from recurrence in the CB group (P = 0.038). Right phrenic nerve palsy (PNP) occurred in 8 patients (16%) in CB‐A group and in 4 patients (8%) in the CB group. Conclusion Freedom from AF on 12 months follow‐up was significantly higher in the CB‐A group with respect to the first generation device. The most frequent complication observed was PNP.